OPTIMIZATION OF EXTRACTION PARAMETERS FOR TOTAL FLAVONOIDS FROM GARDENIA GUMMIFERA GUM RESIN BY RESPONSE SURFACE METHODOLOGY - Bhandare, Snehal B.; Laddha, Kirti S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To optimize the extraction parameters for determining the highest yield of Total Flavonoids from Gardenia gummifera gum resin. Methods: In the present study, response surface methodology (RSM) with three level Box Behenken design (BBD) was performed to optimize extraction parameters for total flavonoids. Solvent concentration(A), extraction time (B) and extraction temperature(C) were considered for single factor experiment. Results: The highest flavonoid concentration was obtained with acetone 45.00% v/v, time 101.46 min, temperature 41.57 Â°C. The average experimental TFC under optimal conditions was 161.14 mg/g which was in close agreement with the predicted value of 163.42 mg/g. Conclusion: RSM-BBD is successfully applied in optimizing extraction conditions for extraction of total flavonoids from G. gummifera gum resin.